Cash Flow Statement: Assesment of Situation and Application problems in Serbia - Miletić, Dragan B (Industrija, 2014)
Time of global economic crisis and unstable financial markets additionally emphasized the fact that inadequate cash flows are frequent serious problem in the operations of economic entities. With the aim to assess the situation and problems in application of cash flow statement and explain reasons of  insufficient affirmation of cash flow statement in business practice in the Republic of Serbia, questionnaire based research was carried out among local companies. The questionnaire consisted of questions aimed at assessing the condition in the abovementioned problem and identifying causes of the recorded situation. The analysis of obtained data included identification of influence of the company size criterion. Obtained results point out that the quality of the preparation and analysis of cash flow statement are, for large companies, in general satisfactory, while for medium and small companies improvements are necessary regarding the existing practices and upgrading of knowledge related to the methodology of preparation of cash flow statement and cash flow analysis by managers and accountants.
Keywords: Causes; Situation; Company size; Republic of Serbia; Cash flow statement